Lymphoedema. Issue 4 (April 2016) - Modarai, Bijan; Lyons, Oliver T.A.
Abstract: Lymphoedema is caused by the failure of lymphatic drainage leading to an accumulation of protein-rich fluid in the interstitium. It can be classified as primary (genetic cause) or secondary. Early diagnosis is essential to prevent progression. In the Western world, lymphoedema is most commonly secondary to cancer and its treatment. In endemic regions, filariasis is an important cause and a global eradication programme is underway. Recently, progress has been made in understanding the embryology of the lymphatic system and specific genetic causes of primary lymphoedema, leading to the hope that medical therapies may improve lymphatic function. Surgery is currently reserved for advanced disease and is performed in specialist centres, primarily to reduce the bulk of swollen tissue.